Breastfeeding Bodies: Intimacies at Work. Issue 1 (6th February 2017) - Lee, Robyn
Abstract : This paper will combine a review of literature on breastfeeding and work with an examination of feminist theory and theories of embodiment. Difficulties accommodating breastfeeding in contemporary workplaces result from problems with how bodies and intimacies are understood. The concept of corporeal generosity is useful in theorizing the intimate relationship involved in breastfeeding. However, it is also essential to recognize that the labour involved in this embodied, relational practice goes largely unvalued. Women's long association with giving has led to the devaluing of reproductive labour and care work. Reconceptualizing work by rethinking the division between productive and reproductive labour is necessary to allow more space for bodies and intimacies.